Be heroic selected minor prophets : Amos, Obadiah, Micah, Zephaniah - Wiersbe, Warren W. (Colorado Springs, CO Chariot Victor, 1996)
Includes bibliographcal references.
Keywords: Bible. O.T. Amos -- commentaries; Bible. O.T. Obadiah -- commentaries; Bible. O.T. Micah -- commentaries; Bible. O.T. Zephaniah -- commentaries